2018
DOI: 10.21608/mnj.2018.175839
|View full text |Cite
|
Sign up to set email alerts
|

Women's Knowledge Regarding Pelvic Organ Prolapse

Abstract: Pelvic organ prolapse is considered as one of the most common causes of reproductive morbidity which influences the women's quality of life. Aim: The present study aimed to assess women's knowledge regarding pelvic organ prolapse. Subjects and Method: The study followed a descriptive design on 220 women with pelvic organ prolapse who were chosen by convenient sample technique. Setting: The study was conducted at Outpatient Gynecological Clinics in the Obstetrics and Gynecology Center at Mansoura City, Egypt ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Therefore, the affected people are less likely to be diagnosed. Women’s awareness of POP is low; this could lead to a lack of reporting and a lack of proper identification of the disease through the questionnaire ( 41 43 ). The sensitivity of the prolapse questionnaire to identify cases of pelvic organ prolapse was very low (38.3) even when clearly visible ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the affected people are less likely to be diagnosed. Women’s awareness of POP is low; this could lead to a lack of reporting and a lack of proper identification of the disease through the questionnaire ( 41 43 ). The sensitivity of the prolapse questionnaire to identify cases of pelvic organ prolapse was very low (38.3) even when clearly visible ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Women's lack of awareness about vaginal prolapse can lead to a variety of major reproductive health issues. As a result, you must exercise greater caution to avoid these issues (Rashad, Fadel & El-Nemer, 2018). As a result, women should be tested for vaginal prolapse knowledge and practice.…”
Section: Significance Of the Studymentioning
confidence: 99%
“…According to the survey, women in underdeveloped countries are more aware of uterine prolapse than those in developed countries. This could be due to variances in the samples' general qualities Rashad (2018). found that women's total knowledge of pelvic organ prolapse related to study-measured age, and there was a correlation between educational attainment and general female features.…”
mentioning
confidence: 97%
“…When husbands do not get sexual satisfaction from UP women, they threaten to take another wife 10 . There are several risk factors for UP, including smoking, improper delivery techniques or delivery through an untrained doctor, heavy lifting, heavy work during and immediately after pregnancy, multiparity, low education, teenage pregnancy, and lack of good nutrition [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%